Bringing the School to the Children : Shortening the Path to EFA - Lehman, Douglas (World Bank, Washington, DC, 2012)
Recent education planning initiatives in West and Central Africa show that the path to EFA may be shortened considerably by reconsidering the way basic education is delivered in isolated rural communities. Since independence, education systems have been expanding rapidly and are now serving most of the easy-to-reach population. For progress to continue, the focus must be shifted toward the sparsely populated areas, which means adjusting the type of schools used, and building them close to where children live. Most out-of-school children live in rural areas. Unfortunately, few rural schools offer the complete primary cycle. A number of factors contribute to the incomplete-cycle phenomenon. The most significant is that the potential student population is insufficient for a three- or six-teacher school. Having children walk to school from neighboring villages also contributes to low enrollment and low student-teacher ratios. Since teachers generally do not teach more than 1 or 2 grades at a time in a classroom, rural communities usually have low student-teacher ratios, and education system administrators cannot justify sending additional teachers to the school. In addition, schools with incomplete cycles tend to have extremely low survival rates.